Vertebrate development requires ARVCF and p120 catenins and their interplay with RhoA and Rac - Xiang Fang; Hong Ji; Si‐Wan Kim; Jae‐Il Park; Travis G. Vaught; Panos Z. Anastasiadis; Malgorzata Ciesiolka; Pierre D. McCrea (2004)
Using an animal model system and depletion-rescue strategies, we have addressed the requirement and functions of armadillo repeat gene deleted in velo-cardio-facial syndrome (ARVCF) and p120 catenins in early vertebrate embryogenesis. We find that xARVCF and Xp120 are essential to development given that depletion of either results in disrupted gastrulation and axial elongation, which are specific phenotypes based on self-rescue analysis and further criteria. Exogenous xARVCF or Xp120 cross-rescued depletion of the other, and each depletion was additionally rescued with (carefully titrated) dominant-negative RhoA or dominant-active Rac. Although xARVCF or Xp120 depletion did not appear to reduce the adhesive function of C-cadherin in standard cell reaggregation and additional assays, C-cadherin levels were somewhat reduced after xARVCF or Xp120 depletion, and rescue analysis using partial or full-length C-cadherin constructs suggested contributory effects on altered adhesion and signaling functions. This work indicates the required functions of both p120 and ARVCF in vertebrate embryogenesis and their shared functional interplay with RhoA, Rac, and cadherin in a developmental context.